Review on applications of sago starch processing effluent - Abdul Malek, Mohd Izhar; Azmi, Azlin Suhaida; Mohamad Puad, Noor Illi (Kulliyyah of Engineering International Islamic University Malaysia P.O. Box 10, 50728 Kuala Lumpur, Malaysia, 2016)
This paper overviews reported studies on the hydrolysis of starch via acid and enzyme. Sago starch processing effluent (SSPE) is a carbohydrate rich waste material that has a potential to be used as a substrate for fermentation process. As it contains high amount of organic compounds, usual practice of disposing it into the nearby river will only lead to the pollution and disruption to ecosystem. Studies have been done to look for the application of the effluent such as for algae cultivation, growth of purple nonsulfur phototrophic bacteria and biofuel production. Acid hydrolysis has a long history for its application to modify starch. However, main disadvantages of acid hydrolysis are relatively low yield and excessive formation of by-products. Enzymatic hydrolysis have become the new alternative where the conventional method of starch hydrolysis using acid has been replaced by the process of using starch saccharifying enzymes such as α-amylase and glucoamylase.